2005
DOI: 10.1159/000086251
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy Improves Compliance with Tuberculosis Treatment

Abstract: Background: Low treatment completion rate in tuberculosis (TB) patients is a major concern. Physicians have always been striving for better treatment adherence in such patients. The present study is one such attempt in this direction. Objectives: The study was aimed to evaluate the role of behavior modification by psychotherapy in improving compliance with short-course anti-TB chemotherapy in India. Methods: It was a prospective controlled trial involving patients with confirmed pulmonary and extrapulmonary TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
(11 reference statements)
1
33
1
Order By: Relevance
“…Another study in India found that individual psychotherapy, utilizing principals of motivational interviewing among drug-sensitive TB patients with no mental illness, contributed to significantly higher rates of treatment adherence (Janmeja et al 2005). In our experience, psychosocial support groups have proved useful in helping patients manage some of the difficulties associated with treatment.…”
Section: Discussionmentioning
confidence: 66%
“…Another study in India found that individual psychotherapy, utilizing principals of motivational interviewing among drug-sensitive TB patients with no mental illness, contributed to significantly higher rates of treatment adherence (Janmeja et al 2005). In our experience, psychosocial support groups have proved useful in helping patients manage some of the difficulties associated with treatment.…”
Section: Discussionmentioning
confidence: 66%
“…10,11,12,13 Moreover stigma also had its direct impact by affecting patients in multiple ways and it has been shown to hinder adherence to treatment. Utilizing principles of motivational interviewing which was found to be effective in improving treatment adherence in India, 14 could be further explored among MDR-TB patients. In addition to educating to patients, their families and employers on MDR-TB it becomes important to help them (patients) understand their problems and help them to overcome both perceived and enacted social stigma.…”
Section: Discussionmentioning
confidence: 99%
“…study conducted in Senegal on CAT-I TB patients showed that in comparison to control group (16.8%), default rate was decreased up to 5.5% in intervention group receiving counselling interventions [15]. Likewise, a study in India suggests that psychotherapy with motivational interviewing techniques among MDR TB patients without any psychological problem significantly enhanced treatment adherence [16].…”
Section: Discussionmentioning
confidence: 97%